Struktur Morfologis sebagai Pembangun Daya Persuasif Iklan Layanan Masyarkat (ILM) Bidang Kesehatan - Lutfitasari, Wevi; Vidiarama, Made Arya; Taembo, Maulid; Ubaidillah, Ubaidillah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study focuses on a morphological analysis of public service advertisements (PSAs) in the health sector. The selection of morphological forms influences the construction of persuasive messages in PSAs. Accordingly, this study aims to examine morphological forms along with their meanings, both morphologically and syntactically, as constituents of the grammatical structure of PSA language containing persuasive elements. In addition, this study seeks to describe the relationship between morphological forms and persuasion in health-related PSAs.This research is categorized as a qualitative descriptive study employing a case study approach. The data consist of morphological forms derived from public service advertisements uploaded by the Health Office of Bangkalan Regency through its official account, @Dinkesbangkalan. Data were collected using documentation techniques and subsequently analyzed using the distributional method. The findings reveal four characteristics of morphological structures in PSAs as constituents of persuasive language. First, the morphological process identified is limited to affixation. Second, the types of affixation include prefixes (peN-, meN-, ber-), confixes (ke-an, peN-an, meN-i), and suffixes (-kan, -i, -an). Third, the resulting morphological forms occupy core syntactic functions, namely Subject and Predicate. Fourth, affixation functions as a marker of instruction or direct persuasion and supports the clarity of commands. In conclusion, the morphological forms found in PSAs are exclusively derived from affixation, functioning both as core elements of sentence structure and as markers of persuasion.